Numerical model of selective external oxidation of Fe-Mn binary alloys during non-isothermal annealing treatment. (January 2021) - Gong, L.; Jiang, W.B.; Balloy, D.; Giorgi, M.-L.
Highlights: A numerical model was developed to describe the kinetics of external selective oxidation of binary Fe-Mn alloys. The numerical model applies to non-isothermal continuous industrial annealing. The model predicts the size of the oxides throughout the non-isothermal annealing process. A parametric analysis of the physical constants involved in the model is conducted. This model is validated for several Mn contents and several thermal profiles. Abstract: A numerical model has been developed to describe the kinetics of selective external oxidation of Fe-Mn alloys during non-isothermal annealing. This model involves a thermodynamic analysis of possible reactions during annealing and then numerically solves the theoretical equations describing reactive diffusion and heterogeneous nucleation and growth of MnO oxides. The results of the model are the temperature-dependent evolution of the nucleation rate of MnO embryos and the size and surface coverage fraction of MnO particles. The results were validated by experimental data. The study concludes with a parametric analysis of the different physical constants of the model.